Auditory processing disorders in incarcerated youth: A call for early detection and treatment. (January 2020) - Berken, Jonathan A.; Miller, Elizabeth; Moncrieff, Deborah
Abstract: Background: Numerous reports have linked language impairment, academic underachievement, and attention disorder to misbehavior in adolescence. Recent studies have found an association between deficits in hearing and auditory processing and involvement in the juvenile justice system. In fact, the existence of an auditory processing disorder (APD) is a risk factor for adolescent delinquency even in the presence of normal hearing. The nexus between APD, low academic achievement and offending behavior in teens has prompted recommendation for early screening of school children for abnormalities in auditory processing. Using a variety of diagnostic tools, investigators have found an increase in the frequency of APD in cohorts of confined youthful offenders. The present investigation evaluates the prevalence of APD in a group of incarcerated youth residing in a detention center. Methods: A total of 52 incarcerated adolescents (8 females and 44 males; age range 13–20 ( M = 16.0), residing at a juvenile detention center in Pittsburgh, Pennsylvania and determined to have normal auditory acuity were included in the study. All participants were screened for APD using two dichotic listening tests, the Randomized Dichotic Digits Test (RDDT) and the Dichotic Words Test (DWT), evaluative modalities to identify deficits in auditory processing. The prevalence of APD in the study group was compared to previously published normative data for non-offending age-matched youth. Results: On the RDDT, 23.1% of participants demonstrated normal auditory processing, while 77% had abnormal test results. On the DWT, 75% of subjects exhibited normal auditory processing, while the scores were abnormal for 24.9%. When the results of the RDDT and the DWT were combined to establish a pattern for the purpose of interpreting a deficit, 21.1% of the participants produced results that were within normal limits, while 17.3% qualified for a diagnosis of APD, with abnormal results on both tests. Previous studies have estimated the prevalence of auditory processing disorder in the general adolescent population as being between 2% and 7%. Conclusions: This study found a higher prevalence of auditory processing disorder in a cohort of incarcerated youth compared with age-matched controls. Diagnostic screening protocols that identify at-risk children have been developed, as have effective therapies to improve auditory processing function. Teachers, pediatricians and psychologists should consider APD in children and adolescents with behaviors that may increase their risk for juvenile justice involvement. Studies on optimal timing and strategies for assessing and treating APD in children and adolescents are needed, including youth caught up in the juvenile justice system.